A Critical Review of the Municipal Public Accounts Committee and Financial Management at Amahlathi Municipality, South Africa - Tando Rulashe; Maggie Nombuyiselo Dyan (JPAS (Journal of Public Administration Studies), 2023)
Despite the existence of the MPAC within Amahlathi municipality, the municipality was placed under an administration which is a clear indication of the failure of the MPAC in executing its functions. This study assesses the challenges that confront Amahlathi municipality MPAC, leading to its failure to execute its mandate. A qualitative research and case study design were adopted for this study. An autopsy of secondary data was done through desktop research and analysed using the content analysis technique. The study revealed that lack of skills, lack of capacity, corruption, uncoordinated systems within the municipality and budgetary constraints impede the work of the municipality. The recommends that MPAC needs support to enhance its effectiveness and efficiency. Literature has shown that the South African government established an impressive legislative framework for local government, however, compliance with the requirements of the frameworks is lacking, particularly in relation to MPAC.